2006
DOI: 10.1007/s10549-006-9162-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PEA3 and Lack of Correlation Between PEA3 and HER-2/neu Expression in Breast Cancer

Abstract: The ETS protein PEA3 functions as a transcription factor to regulate gene expression. Although members of the ETS family have been reported to be involved in tumor progression, ectopic expression of PEA3 has been shown to suppress tumor formation. Despite several studies demonstrated frequent expression of PEA3 and its high association with HER-2/neu and have suggested a potential role of PEA3 in breast cancer, contradictory result has shown that the PEA3 was associated with better survival rate in breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…Another study found PEA3 protein expression in 22.2% (64/289) of breast cancers, but failed to find correlation with HER2/neu expression [83].…”
Section: Pea3mentioning
confidence: 94%
“…Another study found PEA3 protein expression in 22.2% (64/289) of breast cancers, but failed to find correlation with HER2/neu expression [83].…”
Section: Pea3mentioning
confidence: 94%
“…HER2 overexpressing breast cancer cells lines, like BT-474, MDA-453, and ZR-751, show a 30-fold enhanced activity of PEA3 for its binding site on the HER2 promoter. Although the majority of evidence supports a model whereby PEA3 and HER2 are locked in a positive feedback loop, there is some controversy, since a few reports suggest an anti-tumor role of PEA3 in breast cancer and that there is no significant correlation of HER2/Neu and PEA3 expression (Xia et al, 2006, Yu et al, 2006). Evidence for a definitive role of PEA3 downstream of HER2 and in oncogenesis comes from studies using dominant-negative proteins to inhibit signaling steps downstream of HER2 (O’Hagan and Hassell, 1998, Shepherd et al, 2001).…”
Section: B Mechanisms Of Ets Protein Mediated Oncogenesismentioning
confidence: 99%
“…Real-time polymerase chain reaction (RT-PCR) studies showed that down-regulation of HER2 mRNA levels closely correlated with FASN blockade-induced reduction of HER2 protein expression, thus suggesting that changes in HER2 oncogene expression upon pharmacological inhibition of FASN activity resulted from effects at the transcriptional level (22). Indeed, FASN inhibition was found to up-regulate the expression of the Ets class transcription factor PEA3, a potent trans-repressor of HER2 promoter activity that specifically reverses the in vitro transformed phenotype of HER2-overexpressing cancer cells and inhibits HER2-induced tumorigenesis in vivo (30)(31)(32)(33). When transient transfection experiments with a Luciferase reporter gene driven by the HER2 promoter were performed in HER2-overexpressing breast cancer cells, treatment with chemical FASN blockers such as C75 profoundly repressed the constitutive hyperactivity of the HER2 gene promoter (25)(26)(27)(28).…”
Section: Pharmacological Blockade Of Fatty Acid Synthase (Fasn) Revermentioning
confidence: 99%